Development and characterization of acid-induced whey protein concentrate and egg white protein composite gel. (15th July 2022) - Pu, Xueli; Zhang, Mengyuan; Lin, Xudong; Tuo, Yanfeng; Murad, Mian Safian; Mu, Guangqing; Jiang, Shujuan
Abstract: The thermal aggregate solutions were prepared by mixing whey protein concentrate (WPC) and egg white protein (EWP) with different protein mass ratios (3:0, 3:1, 1:1, 1:3, 0:3), and then WPC/EWP composite gels were induced by glucono-δ-lactone (GDL), respectively named WPC, WE3/1, WE1/1, WE1/3, and EWP. The texture properties, water holding capacity, color, thermal stability, rheological and structure properties of the gels were investigated. The results showed that with the increase of EWP content, the hardness, adhesiveness, resilience and gumminess of WPC/EWP composite gels gradually increased. EWP gel exhibited the highest water holding capacity (96.55%). Rheological analysis showed that the storage modulus and loss modulus of the gels showed an increasing trend. EWP gel had the lowest creep flexibility and the strongest resistance to deformation. The DSC test showed the thermal stability of WE1/1 gel was the best (Td =115.84 °C). SEM results showed the three-dimensional network structure of composite gel was more denser with EWP incorporation. The self-supporting gels prepared by mixing whey and egg white protein had more excellent performance than single WPC gel. The information generated from this study may provide opportunities to develop functional food formulations enriched with whey protein and egg white protein. Highlights: Cold-set acid-induced whey protein concentrate/egg white protein composite gels were prepared using glucono-δ-lactone. The creep flexibility and resistance to deformation of acid-induced gels was studied by creep and recovery tests. Whey protein concentrate/egg white protein composite gels showed excellent texture and structural properties.